Assembly of Topic Extraction Module in SUMMARIST - Lin, Chin-Yew (1998 AAAI Spring Symposium, 1998)
Over the past two years we have been developing the text summarization system SUMMARIST. In this paper, we describe the current status of SUMMARIST and its use in TIPSTER Phase III text summarization research.